To save the saver: facilitating school counselors’ occupational well-being through multi-dimensional support and basic psychological needs - Feng, Lina; Liu, Yi; Huang, Haoyan (Frontiers in Psychology, 2024)
School counselors play an increasingly crucial role in protecting students’ mental health. However, many of them have experienced poor well-being in their occupations, which undermines their efficacy in mental protection. To identify the most significant well-being facilitators, this study examined associations between school counselors’ occupational well-being and situational, inter-individual and intra-individual supports, as well as further explored their dynamics. A total of 1,443 Chinese school counselors (66.6% part-time) from a regionally representative dataset were selected, and their work engagement, pressure and satisfaction were surveyed as well-being indicators. Dominance analysis revealed that (1) organizational support and occupational empowerment were consistently robust facilitators for most psychological needs and well-being indicators, (2) students were the most critical supporters for occupational well-being, particularly for part-time counselors; and (3) autonomy and competence were more central needs than relatedness in transferring supports to occupational well-being. Findings implied the most effective strategies to benefit school counselors’ occupational well-being, both in general and across different work cohorts.